What are the causes of murmurs in young children?. Issue 8 (August 2015) - Graham, Cassidy; Deiss, Zach
Abstract : Evidence‐Based Answer : Structural anomalies may be found in up to 43% of newborns with heart murmurs, although only about 5% of newborns with murmurs require early intervention (SOR: C, single retrospective cohort study). In older children referred for evaluation of murmurs, 91% have minor or no structural disease on echocardiography (SOR: B, single retrospective cohort study). Ventricular septal defect (VSD) and atrial septal defect (ASD) are the most common significant anomalies in both neonates and older children.